2014
DOI: 10.1007/s10529-014-1613-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of poly-γ-glutamic acid by a newly-isolated Bacillus subtilis

Abstract: Application of poly-gamma-glutamic acid (γ-PGA), an unusual macromolecular anionic polypeptide, is limited due to the high cost associated with its low productivity. Screening bacterial strains to find a more efficient producer is one approach to overcome this limitation. Strain MJ80 was isolated as a γ-PGA producer among 1,500 bacterial colonies obtained from soil samples. It was identified as Bacillus subtilis, based on the biochemical and morphological properties and 16S rDNA gene sequencing. It produced γ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…There was an increase in γ-PGA production when 10% of the γ-PGA producer was cultivated under optimal culture conditions in a medium that now contained either cassava peel, fructose or Coix leaves with ammonium sulfate, at 25°C and a pH of 5.5, over 48 h to yield 26.45 g/L, 23.23 g/L and 16.87 g/L of γ-PGA, respectively. at 1639.38 cm −1 , carbonyl absorption at 1439.00 cm −1 and hydroxyl absorption at 3417.00 cm −1 -are in agreement with those of other authors 17,19,26 who independently reported a strong amide (N-H) absorption at ~1620-1655 cm −1 , a weaker carbonyl (C=O) absorption at ~1394-1454 cm −1 , a strong hydroxyl (OH) absorption at ~3400-3450 cm −1 , and a characteristically strong amine (C-N) absorption in the range of 1085-1165 cm −1 . Characterization of the γ-PGA produced…”
Section: γ-Pga Production Using Agricultural Residuessupporting
confidence: 93%
See 2 more Smart Citations
“…There was an increase in γ-PGA production when 10% of the γ-PGA producer was cultivated under optimal culture conditions in a medium that now contained either cassava peel, fructose or Coix leaves with ammonium sulfate, at 25°C and a pH of 5.5, over 48 h to yield 26.45 g/L, 23.23 g/L and 16.87 g/L of γ-PGA, respectively. at 1639.38 cm −1 , carbonyl absorption at 1439.00 cm −1 and hydroxyl absorption at 3417.00 cm −1 -are in agreement with those of other authors 17,19,26 who independently reported a strong amide (N-H) absorption at ~1620-1655 cm −1 , a weaker carbonyl (C=O) absorption at ~1394-1454 cm −1 , a strong hydroxyl (OH) absorption at ~3400-3450 cm −1 , and a characteristically strong amine (C-N) absorption in the range of 1085-1165 cm −1 . Characterization of the γ-PGA produced…”
Section: γ-Pga Production Using Agricultural Residuessupporting
confidence: 93%
“…These findings may be attributed to the fact that simple sugars are more desirable for bacterial metabolism since less energy is required to incorporate them into the metabolism of a cell. However, Ju et al 19 obtained a higher γ-PGA yield with 30 g/L of starch in the fermentation medium and B. subtilis MJ80, yielding 48.3 g/L of γ-PGA. The findings that citric acid and starch supported bacterial growth may be attributed to the ease with which these compounds convert into glutamic acids, through the tricarboxylic acid cycle and finally into poly-γ-glutamate.…”
Section: Growth and γ-Pga Production Responses Of Bacillus Toyonensismentioning
confidence: 98%
See 1 more Smart Citation
“…For an exogenous glutamate-independent producer, yeast extract proved to be an excellent nitrogen source for bacterial cell growth and γ-PGA production, but the high cost is a barrier to commercial production [ 51 ]. Therefore, attempts have been made to reduce the dosage or replace it with other media supplements such as (NH 4 ) 2 SO 4 or NH 4 Cl [ 56 ] (Table 1 ). As well as carbon and nitrogen sources, inorganic salts can affect the production, productivity, and quality of γ-PGA.…”
Section: Fermentation Engineering For γ-Pga Productionmentioning
confidence: 99%
“…, respectively). This high production of PGA may be related to the consumption of glucose and NH 4 Cl 2 as carbon and nitrogen sources in this media that classified as one of the most efficient C and N 2 sources [41].…”
Section: Determination Of the Best Pga Productive Mediummentioning
confidence: 89%